Tackling the Challenge of the Total Synthesis of Periploside A - Zhang, Xiaheng; Yu, Biao (Synlett, 2018)
Periploside A is the prototypical congener of the pregnane glycosides occurring in the Chinese medicinal plant Periploca sepium, featuring a unique seven-membered formyl acetal bridged spiro-orthoester (FABO) sugar linkage and potent immunosuppressive activities. This account details our efforts on the stereoselective construction of the FABO motif that has led to a successful total synthesis of periploside A.1 Introduction2 Attempts at Construction of the FABO Motif2.1 Intermolecular Condensation and Transacetalation2.2 Intramolecular Hydrogen Atom Transfer (HAT) Reaction3 Synthesis of the FABO Motif Bearing the Unnatural Anomeric Configuration4 Synthesis of the FABO Motif Bearing the Natural Anomeric Configuration4.1 Unsuccessful Attempts4.2 Final Solution5 Conclusion
Keywords: orthoester; formacetal; deoxysaccharides; dioxocarbenium; conformation; pregnane glycosides; glycosylation